Science Lab Restructuring of a Public School Elementary and High School - Moro, Elisiane da Costa; Francischetti, Eduarda Cardoso; Flores, Giovana Danieli; Fontoura, Juliana de Ávila; Villas-Boas, Valquíria (Scientia cum Industria, 2016)
This paper presents the process of restructuring the science lab of a state school in Caxias do Sul, whose main objective was to create a space where teachers could develop practical and experimental activities with their students. The restructuring of the science lab this school, was only possible through the project "More and Better Students and Teachers in Science, Mathematics, Engineering and Technologies" Initiation Program in Science and Mathematics, Engineering, Creative Technologies and Letters - PICMEL sponsored jointly by the University of Caxias do Sul, the SEDUC-RS, FAPERGS and CAPES. The project was developed at school by a teacher of physics and three high school students. Through the restructuring of the science lab, practical activities were developed and workshops where students had the opportunity to be more active in the process of teaching and learning. With the development of such activities was observed that the students were more willing to learn Science and Mathematics and could relate scientific knowledge to their daily lives, giving greater meaning to their learning. http://dx.doi.org/10.18226/23185279.v3iss3p81